Examining Youth Protections against Gambling in Ireland: A Tiger Team (Red Team) Examination of the National Lottery (Epidemiology, Biostatistics, and Public Health, 2025)
Background: Youth gambling in Ireland is of growing concern.Objectives: Thus, this study evaluated youth gambling protections in the Irish National Lottery’s online age verification system.Methods: A Tiger Team (Red Team) methodology was used. This involved using falsified National Lottery accounts (n = 56).Results: Over half (55.4%) of attempts were successfully verified, with successful verification significantly varying by gender.Conclusions: These findings highlight vulnerabilities in the National Lottery’s online age-verification system and underscore the urgent need for more robust safeguards to prevent underage access.
Keywords: National Lottery; youth protections; gambling; youth gambling; age verification; Ireland; public health